Growth Response of Porphyridium sp. Culture on Glass and Plastic Container in Laboratory Scale - Lutfiyah Al Adawiyah; Mohammad Faizal Ulkhaq; Hapsari Kenconojati (Journal of Aquaculture and Fish Health, 2020)
Utilization of Porphyridium sp. began to be developed as an anticancer, anti-inflammatory, antibacterial, antifungal, and production of biogas and biodiesel so that necessary to carry out culture activities for ensure continuity of Porphyridium sp. This study aims to determine the type of culture container that showed the best growth response of Porphyridium sp. with the highest biomass. The stages in this research were preparation of containers and media sterilization, making diatom fertilizers and agar media, Culture of Porphyridium sp. on agar media, Culture of Porphyridium sp. in the test tube, and Culture of Porphyridium sp. in glass and plastic containers. The results showed that the growth response of Porphyridium sp. that cultured in glass containers (18,9 ± 0,21 x 105 cells/mL) was higher than plastic (15.57 ± 0,03 x 105 cells/ml).